PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI INTRINSIK TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) UP3 MAKASSAR SELATAN - Nuryuli Nuryuli Nuryuli (Universitas Teuku Umar, 2026)
This study aims to analyze the influence of transformational leadership style and intrinsic motivation on employee performance at PT PLN (Persero) UP3 Makassar Selatan. Using a quantitative approach with a causality design, this study involved the entire population of 50 employees as respondents through a total sampling technique. Partial test results (t-test) show that transformational leadership style (t = 3.887; sig = 0.000) and intrinsic motivation (t = 5.082; sig = 0.000) have a positive and significant effect on employee performance. Simultaneously (F-test), both variables significantly influence performance with an F-value of 27.768. The R Square value of 0.542 indicates that these two independent variables contribute 54.2% to employee performance, while the remaining 45.8% is influenced by other factors outside this study.Keywords: Transformational Leadership Style, Intrinsic Motivation, Employee Performance.